2021
DOI: 10.1029/2020ja028809
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variations of Daytime Periodic Ionospheric Disturbances From Beidou GEO TEC Observations Over China

Abstract: Using total electron content (TEC) data from a chain of Beidou geostationary satellite TEC receivers along ∼110°E during 2016-2019, the local time, seasonal, and latitudinal occurrence characteristics of periodic TEC perturbation associated with medium scale traveling ionospheric disturbances (MSTIDs) are investigated. The results show that the daytime periodic ionospheric disturbances appear prominently in winter with dominant periods ∼30-40 min. An interesting feature is that the latitudinal variations of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this context, one may think that the significantly increased occurrence rates of topside irregularities after about 10:00 LT could be linked to MSTIDs. In fact, in a more recent study by Hu et al (2021), a high occurrence of daytime MSTIDs was observed around 10:00-17:00 LT during Equinox in East/Southeast Asia. The daytime MSTIDs were suggested to be induced by gravity waves.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context, one may think that the significantly increased occurrence rates of topside irregularities after about 10:00 LT could be linked to MSTIDs. In fact, in a more recent study by Hu et al (2021), a high occurrence of daytime MSTIDs was observed around 10:00-17:00 LT during Equinox in East/Southeast Asia. The daytime MSTIDs were suggested to be induced by gravity waves.…”
Section: Discussionmentioning
confidence: 91%
“…The TEC perturbations (dTEC) for each satellite‐receiver link were calculated by subtracting the background vertical TEC, which is the moving average value from the original vertical TEC in a time window of 1 hr. Using the short‐baseline array which consists of three GNSS receivers at Hainan, together with the method presented in our previous works (e.g., Hu et al., 2021), the propagation parameters of TEC disturbances were calculated.…”
Section: Instrument and Data Processingmentioning
confidence: 99%
“…The fixed ionospheric pierce points (IPPs) of the Beidou Geostationary (BD‐GEO) satellite C03 were calculated by assuming the F region height 350 km. With the observations made at the three IPPs (the black asterisks in Figure 1a) which formed an approximate rectangular triangle, the propagating velocity and wavelength of the MSTIDs were calculated based on the same method as in previous studies (e.g., Ding et al., 2011; Hu et al., 2021; Sun et al., 2020b). It should be noted that the temporal resolution of the TEC derived at SANY and Ledong is 1 s. The high‐resolution rate of TEC index (HR‐ROTI; Sun et al., 2021a) could be calculated for all the BD‐GEO TEC at the two sites and projected at 100 km altitude (the black dots in Figure 1a) to indicate strong E s occurrences.…”
Section: Methodsmentioning
confidence: 99%
“…Their locations are shown in Figure 1 by red points. The GNSS receivers receive signals from five BDS GEO satellites with a sampling rate of 30 s and provide continuous observational data (Hu et al, 2017(Hu et al, , 2021. In this study, we used the TEC data from three BDS GEO satellites Figures 2 and 3 show two PDES events from airglow observations at the Fuke station during the nights of 8 February and 4 November 2018, respectively.…”
Section: Instruments and Data Setmentioning
confidence: 99%
“…Their locations are shown in Figure 1 by red points. The GNSS receivers receive signals from five BDS GEO satellites with a sampling rate of 30 s and provide continuous observational data (Hu et al., 2017, 2021). In this study, we used the TEC data from three BDS GEO satellites (C03–C05).…”
Section: Instruments and Data Setmentioning
confidence: 99%